ENT 530 Social media Portfolio: Anting Anting / Nor Alia Aqilah Nor Azmi - Nor Azmi, Nor Alia Aqilah (2021)
The Principle of Entrepreneurship is a core subject in UiTM for every Human Resource student. This subject requires to create a Facebook Page for online marketing campaigns project where the students need to utilize the page to market the chosen product by posting 39 content in total that are based with 7 teasers, 16 soft sells, and 16 hard sells followed with the requirement to gain 91 likes engagement in minimum. This project helps in acquiring a better context of the entrepreneurship process and develop entrepreneurial opportunities. Besides that, from this project, students also able to learn the viability of the online business and expand their understanding of business plans. The business that was chosen in proceeding with this project is named Anting Anting. Anting Anting is an online accessories retailer that offers a variety of handcrafted earrings collections with timeless design and affordable price offers. Anting Anting has released three different collections which are Hoop Collections, Pearl Collections, and Gold Collections with the price of RM5.00 in each piece. The collections are 100% brand new which made from antiallergic high-quality stainless steel that is protected from allergic reaction or skin irritation. Embedded with bead and charm that is based with freshwater pearl, silver and gold plated conspire with the theme of white, gold, and beige. This business is solely founded by Nor Alia Aqilah from the product crafting, designing, packaging to the customer and sales service as well as order entry. This business is located at Rawang, Selangor. The corporate mission of this business is “To propose women across Malaysia an assortment of the finest handcrafted, contemporary and authentic accessories at modest prices”. While the corporate vision is “To become the world's most establish accessories brand” followed by the motto of ‘We feeling the joy of serving you wearing best’.